Explaining the Views of Ibn Sina and Al-Ghazali on Games and Physical Exercises and their Relation to the Relationship Between Body and Soul - Heidari, Samira; Vojdani, Fatemeh; Hosseini, Afzal Sadat (Dinamika Ilmu, 2020)
The purpose of this article is to describe Ibn Sina and Ghazali's philosophical views on soul and body on the one hand and to express their views on physical movements on the other hand in order to explain the relationship between their philosophical views on games and physical exercises related to body and soul. The research method was descriptive-analytical. The research findings showed that despite the differences in the philosophical thought of Ibn Sina and Ghazali, in the field of proofs of the soul and the body, there is a similarity between these two thinkers and the relationship between the soul and the body is two-ways. With physical activity in the game, there is an effect on the soul and vice versa. In fact, whenever playing and exercising are done in proportion and the body is active, then the soul will also have fun, and this is based on the effect that the body has on the soul. According to the theory of two thinkers, such a conclusion is that games and physical exercises recreate energy and rejuvenates the body and soul.